ACHANDROPLASTIC MONSTER IN A GOAT - KUMARI, G ARUNA; GOPAL KRISHNA, M V; MADHAVARA0, T; SADASIVARA0, K (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia in goat due to achandroplastic monster is recorded and discussed.